New Perspectives in Statistical Modeling and Data Analysis Proceedings of the 7th Conference of the Classification and Data Analysis Group of the Italian Statistical Society, Catania, September 9 - 11, 2009 - Ingrassia, Salvatore; Rocci, Roberto; Vichi, Maurizio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume provides recent research results in data analysis, classification and multivariate statistics and highlights perspectives for new scientific developments within these areas. Particular attention is devoted to methodological issues in clustering, statistical modeling and data mining. The volume also contains significant contributions to a wide range of applications such as finance, marketing, and social sciences. The papers in this volume were first presented at the 7th Conference of the Classification and Data Analysis Group (ClaDAG) of the Italian Statistical Society, held at the University of Catania, Italy.
Data Modeling for Evaluation -- Data Analysis in Economics -- Nonparametric Kernel Estimation -- Data Analysis in Industry and Services -- Visualization of Relationships -- Classification -- Analysis of Financial Data -- Functional Data Analysis -- Computer Intensive Methods -- Data Analysis in Environmental and Medical Sciences -- Analysis of Categorical Data -- Multivariate Analysis.
Keywords: Statistics; Mathematical statistics; Econometrics; Statistics; Statistical Theory and Methods; Statistics and Computing/Statistics Programs; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law; Econometrics